2014
DOI: 10.1186/2049-2618-2-40
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and quantification of the fungal microbiome in serial samples from individuals with cystic fibrosis

Abstract: BackgroundHuman-associated microbial communities include fungi, but we understand little about which fungal species are present, their relative and absolute abundances, and how antimicrobial therapy impacts fungal communities. The disease cystic fibrosis (CF) often involves chronic airway colonization by bacteria and fungi, and these infections cause irreversible lung damage. Fungi are detected more frequently in CF sputum samples upon initiation of antimicrobial therapy, and several studies have implicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
121
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 103 publications
14
121
0
5
Order By: Relevance
“…Culture-independent studies have revealed the simultaneous presence of numerous bacterial taxa, fungi, and viruses in respiratory samples from CF patients at all stages of life (2)(3)(4)(5)(6)(7)(8). This abundance of microbes colonizing the respiratory tract, and particularly the lower airways, is facilitated by thick airway mucus and deficient mucociliary clearance that result from mutation of the cystic fibrosis transmembrane conductance regulator (CFTR) gene (9)(10)(11).…”
mentioning
confidence: 99%
“…Culture-independent studies have revealed the simultaneous presence of numerous bacterial taxa, fungi, and viruses in respiratory samples from CF patients at all stages of life (2)(3)(4)(5)(6)(7)(8). This abundance of microbes colonizing the respiratory tract, and particularly the lower airways, is facilitated by thick airway mucus and deficient mucociliary clearance that result from mutation of the cystic fibrosis transmembrane conductance regulator (CFTR) gene (9)(10)(11).…”
mentioning
confidence: 99%
“…Quelques études se sont intéressées au mycobiote digestif ou cutané [1,2], très peu ont abordé le mycobiote pulmonaire [3][4][5][6][7]. Pourtant, plusieurs éléments démontrent l'importance de la flore fongique dans les pathologies respiratoires chroniques telles que la broncho-pneumopathie chronique obstructive (BPCO), l'asthme ou la mucoviscidose : (1) les spores (ou conidies) de champignons sont de petite taille (2 à 10 μm), très facilement inhalées.…”
Section: (➜)unclassified
“…À ce jour, quelques études ont analysé et identifié le mycobiote pulmonaire du sujet sain et/ou les profils de mycobiote modifié (ou dysbiose) caractérisant un contexte pathologique spécifique (asthme, mucoviscidose et transplantation pulmonaire). En utilisant les approches de séquençage à haut débit, toutes ces études ont mis en évidence une flore fongique beaucoup plus riche que celle identifiée par méthode conventionnelle (culture et/ou PCR ciblant un pathogène) [3][4][5][6][7]. En effet, ces techniques offrent la possibilité théorique d'identifier toutes les espèces fongiques pré-sentes (y compris celles réfractaires à la culture comme Pneumocystis jirovecii) et de générer des données détaillées, précises et sans a priori sur cette communauté microbienne [3][4][5][6][7].…”
Section: (➜)unclassified
See 2 more Smart Citations